RETRACTED: A study of Zinc ions adsorption by native and chemically modified leaves of earleaf acacia (Acacia auriculiformis) - Nguyen Duc Anh; Shaikhiev Ildar; Kraysman Natalia (E3S Web of Conferences, 2023)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001